Significance of Elevated Synovial Fluid Lactic Acid and Lactate Dehydrogenase Levels in Differentiating Between Septic Arthritis, Inflammatory Arthritis and Non-Inflammatory Arthritis - Erum, Uzma; Umer, Tahira Perveen; Arain, Shafiq-ur Rehman; Ahmed, Muhammad Rashid; Nazir, Lubna (Pakistan Armed Forces Medical Journal, 2022)
Objective: To determine the lactic acid and lactate dehydrogenase levels in synovial fluid and differentiate between inflammatory and non-inflammatory arthritis. Study Design: Cross-sectional study. Place and Duration of Study: Department of Rheumatology, Liaquat National Hospital, Karachi, from Feb to May 2019. Methodology: All patients of age >18 years, of either gender, who presented with knee joint effusion were enrolled in the study. Synovial fluid aspiration for the analysis of lactate and lactate dehydrogenase (LDH) was done for all patients. Results: Seventy-seven patients were enrolled, of which 75 were included in the analysis. Two patients were excluded as one had lymphoma and the other had recent joint trauma. 31 (41.3 %) patients had non-inflammatory, or osteoarthritis, and 44 (58.7 %) had inflammatory arthritis. The mean value of synovial LDH in inflammatory and non-inflammatory arthritis was 737.38 ± 102.76 mmol/L and 265.5 ± 17.43 mmol/L, respectively, (p<0.001). The mean value of synovial lactate in inflammatory arthritis (32.16 ± 2.84 mmol/L) was higher than the mean value of synovial lactate in non-inflammatory arthritis (19.81 ± 1.08 mmol/L) (p<0.001). There mean plasma LDH in inflammatory arthritis and non-inflammatory arthritis was 495.77 ± 41.67 mg/dl and 437.90 ± 30.99 mg/dl, respectively (p>0.05). The plasma lactate in inflammatory arthritis and noninflammatory arthritis was 12.84 ± 0.59 mg/dl and 12.97 ± 0.78 mg/dl, respectively (p>0.05). Conclusion: Synovial fluid lactic acid and synovial LDH can serve as rapid diagnostic and cost-effective tests to differentiate between non-inflammatory and inflammatory arthritis.